Stereochemistry of Astaxanthin Biosynthesis in the Marine Harpacticoid Copepod Tigriopus Californicus - Prado-Cabrero, Alfonso (Mar Drugs, 2020)
The harpacticoid copepod Tigriopus californicus has been recognized as a model organism for the study of marine pollutants. Furthermore, the nutritional profile of this copepod is of interest to the aquafeed industry. Part of this interest lies in the fact that Tigriopus produces astaxanthin, an essential carotenoid in salmonid aquaculture. Here, we study for the first time the stereochemistry of the astaxanthin produced by this copepod. We cultured T. californicus with different feeding sources and used chiral high-performance liquid chromatography with diode array detection (HPLC-DAD) to determine that T. californicus synthesizes pure 3S,3’S-astaxanthin. Using meso-zeaxanthin as feed, we found that the putative ketolase enzyme from T. californicus can work with β-rings with either 3R- or 3S-oriented hydroxyl groups. Despite this ability, experiments in the presence of hydroxylated and non-hydroxylated carotenoids suggest that T. californicus prefers to use the latter to produce 3S,3’S-astaxanthin. We suggest that the biochemical tools described in this work can be used to study the mechanistic aspects of the recently identified avian ketolase.